Agent-based vulnerability model for pedestrians exposed to urban floodwaters - Li, Qijie; Xia, Junqiang; Xu, Zheng; Liang, Dongfang; Hinkelmann, Reinhard (Journal of Hydrology, 2025)
Climate change-induced floods will have a profound impact on densely populated urban areas. The survey results indicate that a substantial proportion of respondents engaged in evacuation behavior during urban flooding events. However, current assessment methods may underestimate the impact of human motions in floodwaters on pedestrian evacuation safety. To quantitively study the dynamic vulnerability of individuals exposed to flooding scenarios, an agent-based vulnerability model was proposed based on mechanics modelling and experimentally calibrating. A full-scale physical testing platform was constructed and utilized to calibrate the proposed model and to determine the stability limits of pedestrian safety in floodwaters. Spatial and temporal dynamic characteristics of pedestrians were analyzed and results reveal significant variations in pedestrian movement and stability. The general temporal trend of movement speed changing as a power function of the specific flood force has been validated. It is also found that pedestrian stability is notably affected by movement in floodwaters, particularly when walking against the flow, which intensifies the risk of instability, leading to vulnerability indices that increase by 123.2 % at a depth of 0.3 m and by 82.7 % at 0.5 m compared to still-water conditions. In contrast, moving with the flow reduces hydrodynamic forces, although the rate of this reduction decreases with greater water depths, dropping to 16.0 % at 0.5 m and 9.7 % at 0.7 m. Additionally, this work provides guidelines for assessing pedestrian evacuation vulnerability that enhances evacuation safety and supports flood management. © 2025 Elsevier B.V.
Publisher: Elsevier B.V.

Morphological adjustment of the Qingshuigou channel on the Yellow River Delta and factors controlling its avulsion - Zheng, Shan; Han, Shasha; Tan, Guangming; Xia, Junqiang; Wu, Baosheng; Wang, Kairong; Edmonds, Douglas A. (CATENA, 2018)
The avulsion time scale of channels on the Yellow River delta (YRD) is about a decade due to the large sediment load, and rapid channel aggradation and progradation. Nevertheless, the Qingshuigou channel has been maintained for about four decades since 1976. This channel provides an ideal opportunity to study channel evolution following avulsion and to examine different avulsion criteria. In this study, we analyzed the geomorphic adjustment of the lower Qingshuigou channel during 1976–2015, and calculated normalized gradient advantage and superelevation at the channel to estimate how close the channel was to avulsion. Results showed that channel evolution processes may be divided into four phases: I (1976–1980) rapid aggradation, II (1980–1985) channel widening and enlargement, III (1985–1996) main channel aggradation and shrinkage, and IV (1996–2015) main channel incision and deepening. Evolution phases I, II and III are similar to the avulsion cycle observed in natural and experimental fluvial systems. The calculated values of normalized gradient advantage and superelevation in early 1990s exceeded the critical values suggested by previous studies, implying that the channel was prone to avulsion. Nevertheless, avulsion was prevented mainly due to limited overbank flows, constriction from artificial dikes, and slowed channel extension as a result of reduced sediment load. The evolution of the Qingshuigou channel confirms previous arguments that superelevation and gradient advantage are not sufficient for avulsion, and multiple factors should be considered, including flood frequency, lateral mobility, sediment diameter, and human interruptions.
Keywords: Ouvrage_Collectif_Numéro1